DETERMINANTS OF UTILIZATION AND OPTIMUM USE OF FARMER FIELD BUSINESS SCHOOL RECOMMENDATIONS AMONG MAIZE FARMERS IN NORTH WEST NIGERIA - Isemin Effiong, Mercy; Shehu, Abbas; Gwadabe, Mohammed; Francis, Makwin (Applied Studies in Agribusiness and Commerce, 2026)
This study examined the predictors of utilization and intensity of use of Farmer Field Business School (FFBS) recommendations among maize farmers in North West Nigeria. A structured questionnaire was administered to 231 FFBS participants in Kaduna and Kano States. Data were analysed using weighted mean scores, a Utilization Index, Probit regression for the binary utilization decision, and Tobit regression for intensity of use. Results showed that 95.7% of participants utilized FFBS recommendations, yielding a mean Utilization Index of 0.7415. Intensity of use varied widely across practice areas: planting and fertilizer application recorded the highest intensity (WM = 2.49 each), while use of Aflasafe and field measurement returned low scores (WM = 1.39 and 1.58). The Probit model identified sex (p < 0.10), age (p < 0.10), household size (p < 0.05), and land acquisition mode (p < 0.01) as significant determinants of the utilization decision. The Tobit model showed that marital status (p < 0.05), household size (p < 0.10), frequency of extension visits (p < 0.01), and the Perception Index of FFBS (p < 0.01) significantly influenced optimum use. These findings underscore the importance of targeted extension engagement and positive programme perception in deepening practice uptake among smallholder farmers.